Ответы и объяснения

2013-03-22T18:54:39+04:00

По формуле sin(α-β)=sinα*cosβ -sinβ*cosα   получаем                                                                   1)sin(5x-x)=0                                                                                                                                                     2)4x=пk                                                                                                                                                               3)x=пk/4